Evaluasi Keamanan Komunikasi Data Pada Sistem Informasi Cloud Menggunakan Enkripsi End-to-End - Meta Susanti; Gusmayeni Gusmayeni; Umi Khaerunnisa (Bulletin of Information System Research, 2026)
The use of cloud computing technology is increasingly widespread due to its ability to facilitate the storage, management, and exchange of information over the internet. However, cloud-based systems also face security risks such as eavesdropping, theft, data manipulation, and unauthorized access. To address these risks, a security mechanism is needed that ensures the confidentiality, integrity, and availability of information. This study aims to analyze data communication security in cloud-based information systems by implementing the End-to-End Encryption (E2EE) method with the Advanced Encryption Standard (AES) 256-bit algorithm. The research method used an experimental approach with a quantitative descriptive approach. The test environment was built using Docker and the Nginx web server on the Windows Subsystem for Linux (WSL). Security evaluations were conducted based on the Confidentiality, Integrity, and Availability (CIA Triad) concept. The data encryption and decryption processes utilized OpenSSL with AES-256, while service testing was conducted using Nmap and vulnerability analysis using Nessus Essentials. The results showed that AES-256 can convert plaintext into ciphertext that is unintelligible without the decryption key. Integrity testing proved that the decrypted data was identical to the original data, thus maintaining its integrity. Availability was demonstrated by the web server remaining active on port 8080. Furthermore, the Nessus scan found no vulnerabilities with a significant risk level, only those in the informational category. In conclusion, the implementation of E2EE using AES-256 effectively improves the security of cloud-based data communications by meeting the key indicators of the CIA Triad